Kontribusi Ki Bagus Hadikusumo dalam Sidang BPUPKI Mei-Juli 1945 - Yusuf Budi Prasetya Santosa; Rina Kurnia (Universitas Muhammadiyah Prof. Dr. Hamka, 2021)
Abstract In the field of political struggle, the leaders of the national movement were jointly preparing for an independent Indonesia. One of the efforts to prepare for Indonesian independence was through the BPUPKI session which took place from May to July 1945. BPUPKI was the preparation committee for Indonesian independence in the form of Japan which was originally used as a propaganda tool but instead used as a means of struggle for national movement figures. National movement figures who sit in BPUPKI come from various religious and ideological backgrounds. One of the national movement figures who became a member of BPUPKI was Ki Bagus Hadikusumo. Ki Bagus Hadikusumo is the leader of the Islamic organization, Muhammadiyah, which contributed to fighting for and fighting for Indonesian independence through BPUPKI. This study intends to find out about how Ki Bagus Hadikusumo's contribution to the trial of BPUPKI in May-July 1945. The method used in writing this article is a literature study. The results of the study revealed that Ki Bagus Hadikusumo made a big contribution to the BPUPKI session. There are two things put forward by Ki Bagus Hadikusumo, first is the concept of an independent Indonesia, which is a state that is run on the sovereignty of the people, and secondly, fighting for Islam as the legal foundation for an independent Indonesian state. Keywords : BPUPKI, Ki Bagus Hadikusumo, Islam Abstrak Di medan perjuangan politik para tokoh pergerakan nasional bersama-sama mempersiapkan Indonesia merdeka. Salah satu upaya dalam rangka mempersiapkan kemerdekaan Indonesia ialah melalui sidang BPUPKI yang berlangsung dari Mei hingga Juli 1945. BPUPKI merupakan panitia persiapan kemerdekaan Indonesia bentukkan Jepang yang semula digunakan menjadi alat propaganda, namun justru dijadikan sebagai alat perjuangan bagi para tokoh pergerakan nasional. Para tokoh pergerakan nasional yang duduk di dalam BPUPKI berasal dari berbagai latar belakang agama dan ideologi. Salah satu diantara tokoh pergerakan nasional yang menjadi anggota dari BPUPKI adalah Ki Bagus Hadikusumo. Ki Bagus Hadikusumo adalah pemimpin organisasi Islam, Muhammadiyah yang turut berkontribusi dalam memperjuangkan dan memperisapkan kemerdekaan Indonesia melalui BPUPKI. Penelitian ini bermaksud mencari tahu mengenai bagaimana kontribusi Ki Bagus Hadikusumo dalam persidangan BPUPKI Mei-Juli 1945. Metode yang digunakan dalam penulisan artikel ini yaitu studi pustaka. Hasil kajian mengemukakan, bahwa Ki Bagus Hadikusumo memberikan kontribusi yang besar dalam sidang BPUPKI. Terdapat dua hal yang dikemukakan oleh Ki Bagus Hadikusumo, pertama ialah konsep negara Indonesia merdeka adalah negara yang dijalankan atas kedaulatan rakyat, dan kedua memperjuangkan Islam sebagai pondasi hukum bagi negara Indonesia merdeka. Kata kunci : BPUPKI, Ki Bagus Hadikusumo, Islam